环境保护与公平的国际秩序 - Rolston, Holmes, 1932-2025, author; Chinese Society for Environmental Ethics, publisher (Colorado State University. Libraries, 1999)
The UNCED Earth Summit established two new principles of international justice: an equitable international order and protection of the environment. UNCED was a significant symbol, a morality play about environment and economics. Wealth is asymmetrically distributed; approximately one-fifth of the world (the G-7 nations) produces and consumes four-fifths of goods and services; four-fifths (the G-77 nations) get one-fifth. This distribution can be interpreted as both an earnings differential and as exploitation. Responses may require justice or charity, producing and sharing. Natural and national resources come into tension with the common heritage of humankind, exemplified in disputes about who owns biodiversity resources. Ethics has to learn planetary home economics.
Environmental protection and an equitable international order: ethics after the Earth Summit
Text in Chinese.
Translated by Li Shili
Keywords: environmental justice; distribution of wealth; sustainability; equitable international order; UNCED; United Nations conference on environment and development; common heritage of humankind; natural resources; national resources